INTERNAL CONTROL SYSTEM AGAINST REVOLVING FUND OF BUM DESA BERSAMA KALIDAWIR (ANALYSIS OF SHARIA ECONOMY) - Rusmawati, Ayu; Tafakkur, M Bujang; Siswahyudianto, Siswahyudianto (Universitas Islam Negeri Alauddin Makassar, 2017)
Internal control over revolving funds that are not used according to the needs of the debtor and internal control if revolving funds still exist but are not used for group revolving. This internal control is to avoid fraud or embezzlement of BUM Desa Bersama Kalidawir funds. So that revolving funds are used as portions. Private and public institutions always have procedures in carrying out every activity. Likewise, BUM Desa Bersama Kalidawir has a procedure in carrying out an internal control system for revolving funds.